Examining the Relationship between Ethical Climate and Organizational Commitment with the Mediating Role of Organizational–Professional Conflict in Educational Settings of Physical Education and Sport Sciences - Shams, Farahnaz; Gholami, Naser (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to examine the relationship between ethical climate and organizational commitment among physical education teachers in Iran, focusing on the mediating role of organizational–professional conflict.Methods and Materials: A correlational–descriptive design was used. The statistical population consisted of all physical education teachers in Iran (N ≈ 27,000). Based on Cochran and Sharp’s formula, 476 participants were selected through random sampling. Data were collected using four standardized instruments: the Ethical Climate Questionnaire (Cullen et al., 1993), the Organizational–Professional Conflict Questionnaire (Shafer et al., 2002), the Affective Commitment Scale (Meyer & Allen, 1984), and the Impression Management Scale (Paulhus, 1991). Cronbach’s alpha coefficients ranged from 0.76 to 0.89, confirming acceptable reliability. Data were analyzed using Pearson correlation and hierarchical regression analysis via AMOS software, with significance set at p < 0.05.Findings: Results revealed that ethical climate dimensions significantly influenced both organizational–professional conflict and affective commitment. Egoistic/individual, egoistic/cosmopolitan, and benevolent/local climates negatively predicted organizational–professional conflict, whereas principled/individual and principled/cosmopolitan climates showed positive effects. Ethical climate variables accounted for 47% of the variance in organizational–professional conflict and 37% in affective commitment. Organizational–professional conflict exhibited a significant negative correlation with affective commitment but did not mediate the relationship between ethical climate and commitment. Impression management significantly influenced reported perceptions of ethical climate and commitment, indicating potential social desirability bias.Conclusion: The ethical climate in educational organizations plays a pivotal role in shaping teachers’ commitment and managing professional conflicts. Benevolent and principled ethical climates foster stronger affective commitment, whereas egoistic climates undermine it. However, organizational–professional conflict does not function as a mediator in this relationship. Enhancing ethical awareness, fairness, and supportive communication among educational managers can improve teachers’ affective commitment and organizational harmony.